Completion of tuberculosis preventive treatment with 300 mg vs. 100 mg isoniazid tablets: a pragmatic randomized clinical trial - João Paulo Cola; Thiago Nascimento do Prado; Bárbara Manuella Cardoso Sodré Alves; Carolina Maia Martins Sales; Bárbara Juliana Pinheiro Borges; Keila Cristina Mascarello; Anne Caroline Barbosa Cerqueira Vieira; Silvia das Dores Rissino; Wildo Navegantes de Araújo; Noemia Urruth Leão Tavares; Ethel Leonor Noia Maciel (BMC Infectious Diseases)
Abstract Background Monotherapy with the drug isoniazid (INH) was for a long time the main therapeutic regimen used for tuberculosis preventive treatment (TPT). Research is progressing into the use of new therapeutic regimens that provide more complete TPT. The objective was to analyze the completion and safety of TPT with the drug INH in the form of 300 mg tablets. Methods Pragmatic, randomized, non-blinded, multicenter clinical trial conducted in Brazil from January 2019 to December 2022. Subjects over the age of 18 years with an indication for TPT was included and those whose index case of active tuberculosis was in retreatment, multidrug-resistant and extremely resistant, transferred, and people deprived of their liberty was excluded. The intervention was TPT with 1 INH 300 mg tablet and the control group with 3 INH 100 mg tablets. The primary outcome was TPT completion. Pearson's chi-square test was used to analyze the association of TPT completion. The risk of TPT completion was estimated by Poisson regression. The mean treatment effect was calculated. The results were expressed as a risk ratio (RR) with a 95% confidence interval (95%CI). Results A total of 207 individuals were included, 103 (49.7%) in the intervention group. Seventy-two (69.9%) of the individuals who used INH 300 mg completed TPT. The risk ratio for completing TPT was 1.39 times higher in the group that used the INH 300 mg treatment (RR 1.39, 95%CI 1.08 to 1.79). The mean effect of the intervention was 19% (Coefficient 0.19, 95%CI 0.06 to 0.32). There was no significant difference in adverse events between the groups. Conclusion The pragmatic use of INH 300 mg in TPT showed a positive effect on the treatment completion rate and is a safe presentation for use in INH monotherapy regimens. Trial registration The protocol is registered in the Brazilian Registry of Clinical Trials under the code RBR-2wsdt6 in September 2019 10th.